Prophet Muhammad and the Market Governance of Medina: The Institutional Framework of Price Stability in Historical Perspective - Taufik Wahyu Nugroho; Wahyudhi Ramadhan; M. Septyan Rizky; Hendra Syahputra; Fahmi Syahab (Hamidah: Jurnal Ilmu Hadis, 2026)
Price instability and exploitative practices such as hoarding and monopoly characterized the Medina market during the early transitional phase of Islam. Yet, Islamic economic studies tend to frame the issue of tasʻīr normatively, thereby ignoring the historical and institutional configurations that shape price stability. This study aims to analyze the institutional framework of the Prophet Muhammad’s market governance, measuring it against four main dimensions: market structure, regulation, authority, and economic ethics, in maintaining price stability without coercive intervention. This research is a qualitative-historical study based on a literature review, using an institutional analysis approach and drawing on sources such as hadith, sīrah Nabawiyah, and Islamic economic history literature, and analyzing them through thematic analysis and historical-contextual interpretation to systematically reconstruct market practices. The results show that price stability is formed through the integration of interrelated institutional mechanisms, including the establishment of an open market that eliminates barriers to entry and encourages competition, the enforcement of anti-monopoly and anti-hoarding regulations to suppress structural distortions, the internalization of transaction ethics based on justice, transparency, and the prohibition of gharar to reduce information asymmetry, and the strengthening of the legitimacy of the Prophet’s moral authority as a non-coercive compliance mechanism. These findings confirm that price stability results from institutional arrangements that simultaneously manage market behavior and structure. This research repositions price stability as a product of institutional governance and moral legitimacy within a specific historical context, rather than simply the result of administrative intervention.